Using Crank-Nicolson Numerical Method to solve Heat-Diffusion Problem - Omar Abdullah Ajeel; Awni M. Gaftan (Tikrit Journal of Pure Science)
The current study aimed to use the Crank-Nicolson numerical method to solve Heat-Diffusion Problem in comparison with the ADI method. In this paper, the general formula of the Crank-Nicolson Numerical Method was derived and applied to solve the heat diffusion. The same problem then has been solved using ADI numerical method. The results of the Crank-Nicolson numerical method were compared with that of the ADI numerical method. The comparison results revealed that Crank-Nicolson is more accurate than the results of ADI at the initial steps of the problem solution.